HUBUNGAN KOMPENSASI KOMPETENSI MOTIVASI TERHADAP KINERJA DOSEN DI SEKOLAH TINGGI ILMU KESEHATAN NGUDIA HUSADA MADURA - Hidayanto, Nur (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Lecturers as teachers are at the forefront in college, strategic and responsible role in preparing their students into the next generation that is able to compete in the era of globalization, for the sake of progress and the existence of Indonesia in the future. That in carrying out its duties lecturers need to improve the professionalism with full responsibility and discipline as well as get their rights, always motivated in a conducive environment, free from problems and technical barriers, and the availability of adequate facilities and infrastructure. The purpose of this study was to analyze the relationship of compensation, compensation and motivation with performance of high school professor of Sekolah Tinggi Ilmu Kesehatan Ngudia Husada Madura. The study was observational analytic with cross sectional, population in this study are all tenured faculty STIKes Ngudia Husada Madura which numbered 52. The sampling technique used is total sampling. There is a link compensation to performance lecturers. There is a significant relationship between competence by lecturer performance. There is a relationship of motivation with the performance of lecturers. Motivation simultaneously having an influence on the performance of lecturers compared Compensation and competence factor. A review of the method of determining the policy on granting compensation to employees. Giving equal opportunity in the form of training for lecturers. Providing motivation for faculty to do the job in the college environment. Keywords: Compensation, Competency, Motivation, Performance Lecturer.